Preliminary core sets of measures for disease activity and damage assessment in juvenile systemic lupus erythematosus and juvenile dermatomyositis - Ruperto, Nicolino; Ravelli, Angelo; Murray, Kevin J.; Lovell, Daniel J.; Andersson-Gare, Boel; Feldman, Brian M.; Garay, Stella; Kuis, Wietse; Machado, Claudio [UNESP]; Pachman, Lauren; Prieur, Anne-Marie; Rider, Lisa G.; et al. (Oxford University Press (OUP), 2003)
Objective. To identify preliminary core sets of outcome variables for disease activity and damage assessment in juvenile systemic lupus erythematosus (JSLE) and juvenile dermatomyositis (JDM). Methods. Two questionnaire surveys were mailed to 267 physicians from 46 different countries asking each member to select and rank the response variables used when assessing clinical response in patients with JSLE or JDM. Next, 40 paediatric rheumatologists from 34 countries met and, using the nominal group technique, selected the domains to be included in the disease activity and damage core sets for JSLE and JDM. Results. A total of 41 response variables for JSLE and 37 response variables for JDM were selected and ranked through the questionnaire surveys. In the consensus conference, domains selected for both JSLE and JDM activity or damage core sets included the physician and parent/patient subjective assessments and a global score tool. Domains specific for JSLE activity were the immunological tests and the kidney function parameters. Concerning JDM, functional ability and muscle strength assessments were indicated for both activity and damage core sets, whereas serum muscle enzymes were included only in the activity core set. A specific paediatric domain called 'growth and development' was introduced in the disease damage core set for both diseases and the evaluation of health-related quality of life was advised in order to capture the influence of the disease on the patient lifestyle. Conclusions. We developed preliminary core sets of measures for disease activity and damage assessment in JSLE and JDM. The prospective validation of the core sets is in progress.
Keywords: Consensus; Core set; Disease activity assessment; Disease damage assessment; Juvenile dermatomyositis; Juvenile systemic lupus erythematosus; muscle enzyme; child development; child growth; childhood disease; controlled study; dermatomyositis; diagnostic test; disease activity; enzyme blood level; functional assessment; health survey; human; immunology; international cooperation; kidney function; laboratory test; lifestyle; measurement; medical assessment; medical parameters; medical specialist; muscle strength; outcomes research; parent; perception; physician; postal mail; priority journal; quality of life; questionnaire; rating scale; scoring system; statistical analysis; systemic lupus erythematosus; validation process; Child; Clinical Trials; Delphi Technique; Dermatomyositis; Humans; Lupus Erythematosus, Systemic; Prospective Studies; Questionnaires; Severity of Illness Index; Treatment Outcome